“Estudio y diseño del sistema de alcantarillado sanitario, pluvial y tratamiento de aguas servidas de la comunidad nueva esperanza del cantón camilo Ponce Enríquez, provincia del Azuay” - Izurieta Montalvo, Luis Adrian (2015)
Canton Camilo Ponce Enriquez, is the youngest Canton of the Province of Azuay was created according to the official record on March 28, 2002, is located 200 km southwest of the city of Cuenca, west of the province of Azuay , its population is 21,998 inhabitants according to the latest census conducted by the INEC in 2010. it has a land area which covers an area of ​​644 km2 the Canton is divided into two parishes: Urban Parish of the same name (header cantonal) and the Rural Parish El Carmen de Pijilí. At present, the development of peoples depends mainly on a good supply of basic services such as: Potable Water and Sanitation with their respective treatments, which are essential for human life and the environment, all this demand for a correct and optimal health structure ensuring socio-economic development of the city. The increase in population and basic services has led to health inefficiency, New Hope Community does not have a sanitary sewer system, this causes the urgency of technically conduct a study and design Sanitary Sewer System-Stormwater and Sewage treatment. The realization of this important project will improve the urban landscape, living conditions and health of the inhabitants of this community, as improving sanitary conditions, helps to control pollution, improve and protect the environment and natural resources.